APPS E-NTEGRATION: INTEGRATED DIGITAL ASPIRATION SPACE FOR STUDENTS - Eva Agus Triana; Fajar Harry Akbar; Dini Sri Istiningdias; Fajar Hariyanto (Jurnal Riset Komunikasi, 2022)
AbstractThe student movement is always motivated by lofty ideals as a representation of society in fighting for justice and prosperity through consolidation and demonstrations. Various student obstacles in representing community aspirations are very complex. Starting from the emergence of provocateurs, students who just joined in, clashes with security officers, disturbing security, anarchist demonstrations that cause casualties. This paper aims to provide solutions in the form of application innovation which includes application interface design, parties involved, planning analysis, implementation, and application implications that contain menu elements according to student needs in conveying public aspirations in an integrated manner. This research uses literature study as the main reference. Students must move intelligently, utilizing technology and social media as tools to convey aspirations with high intellectual power. The E-integration application is here to answer students' concerns. Apart from conveying aspirations, students also learn to improve literacy through reading, understanding, and listening.